PENGARUH KEBIJAKAN DIVIDEN DAN STRUKTUR MODAL UNTUK MENGUKUR NILAI PERUSAHAAN PT MANDOM TBK PERIODE 2014-2023 - Cahya Ningrum; Jamaluddin (Journal of Research and Publication Innovation, 2025)
This study aims to test whether or not there is an Influence of Dividend Policy and Capital Structure to Measure Company Value at the Cosmetic Company PT Mandom Tbk for the period 2014-2023. This research is a quantitative study. This study uses the annual financial statements of cosmetic companies listed on the Indonesia Stock Exchange as the population. Data collection used in this study was carried out by processing various articles, journals as reference books and other written media related to the topics discussed in the study. The method used is purposive sampling with a sample size of 8 data units. Descriptive statistical methods, classical assumption tests with normality tests, multicollinearity tests and heteroscedasticity tests, autocorrelation tests, hypothesis tests, namely multiple linear regression and t-tests, f-tests and coefficients of determination (R2). Partial testing with the t-test shows that capital structure has a negative and significant effect on company value and dividend policy has no effect on company value. Simultaneous testing results with f with a significance level of 0.05 (5 %). The results of this study indicate that partially Dividend Policy has a significant effect on Company Value, this is evidenced by (t-test) that the t-count value (-1.019) <t-table (2.30600) and shows a significance value of 0.342 where 0.342> 0.05. Partially Capital Structure does not have a significant effect on Company Value, this is evidenced by (t-test) that the t-count value (-1.418) <t-table (2.30600) then shows a significance value greater than α which is 0.199> 0.05. Then simultaneously with (f-test) that the F-count value is 1.823 <F-table 4.74 then shows a significance value of 0.231 <0.05, it can be concluded that Dividend Policy and Capital Structure simultaneously have a significant effect on Company Value.